Blood-retinal barrier permeability and its relation to progression of retinopathy in patients with type 2 diabetes. A four-year follow-up study. - Cunha-Vaz, JG (2010)
Forty patients with late-onset diabetes (age at diagnosis 30 years or more) and minimal retinopathy as found by fundus photography were followed prospectively by repeated examination (baseline, 1 year, and 4 years). The study shows that early retinopathy changes are not permanent or invariably progressive. In the 1st year of follow-up microaneurysms worsened in 25%, improved in 10%, and remained stabilized in 65%. Vitreous fluorometry was able to detect an overall increase of 0.84 +/- 1.06 x 10(-6) min-1 in blood-retinal barrier (BRB) penetration ratios. After 4 years, 16 of the 40 patients had undergone photocoagulation (focal photo-coagulation in 11 and pan retinal photocoagulation in 5). The eyes that needed photocoagulation were the eyes that had higher fluorometry penetration ratios at the patient's entry into the study and showed a higher rate of deterioration during the 1st year of the study (5.54 +/- 1.97 vs 3.11 +/- 1.22 x 10(-6) min-1, P < 0.001, initial values; 1.52 +/- 0.76 vs 0.45 +/- 0.99 x 10(-6) min-1, P < 0.001, annual increase in leakage). The eyes that did not need photocoagulation, 24 out of 40, showed stable fluorometry readings within the 4-year period of follow-up (+0.02 +/- 0.98 10(-6) min-1). Abnormally high vitreous fluorometry values and their rapid increase over time appear to be good indicators of rapid progression and worsening of the retinopathy.